Floristic Diversity and Carbon Sequestration in Shade-Grown Coffee Agroforestry Systems of Chikkamagaluru, Western Ghats - Patil, Somashekhargouda; Rudragouda, C.; Nagaraja, J. S.; Senthilkumar, M.; Sathish, B. N.; Nadaf, Anwar (European Journal of Applied Sciences, 2025)
Coffee-based agroforestry systems offer a synergistic blend of ecological and economic benefits, especially in biodiversity-rich regions like the Western Ghats of India. This study, conducted at the Central Coffee Research Institute (CCRI), Balehonnuru, Chikkamagaluru district, Karnataka, to assess the floristic diversity, aboveground biomass and carbon storage potential in coffee-based agroforestry systems. A total of 115 tree species were identified, indicating high floristic diversity, with species richness ranging from 59 to 80 across the blocks. Total enumeration of tree species above 30 cm GBH was performed across four blocks (A–D), encompassing a total area of 90.8 ha. Species richness varied significantly, with Block D exhibiting the highest diversity (80 species) and Block B the lowest (59 species). The Shannon–Wiener diversity index (Hʹ) ranged from 2.65 (Block B) to 3.44 (Block D), while Simpson’s index (D) confirmed the highest heterogeneity in Block D (D = 0.36). Tree density ranged from 93.5 to 116.0 stems ha⁻¹, with Block A showing the highest basal area (34.04 m² ha⁻¹) and Block C the lowest (20.25 m² ha⁻¹). Aboveground biomass varied from 91.4 t ha⁻¹ (Block C) to 113.9 t ha⁻¹ (Block A), translating into carbon stocks of 45.7 to 57.0 Mg ha⁻¹, respectively. Notably, although Block D exhibited the highest species diversity, it stored only 46.0 Mg ha⁻¹ of carbon, indicating a potential trade-off between biodiversity and biomass. Importance Value Index (IVI) analysis revealed Grevillea robusta as the most dominant species (IVI = 35.80), followed by Ficus virens (IVI = 27.43), reflecting both structural and ecological significance. These findings highlight the multi functionality of coffee agroforestry systems, where structurally mature stands like Block A contribute significantly to carbon sequestration, and biodiverse stands like Block D bolster ecological resilience. This dual role emphasizes the importance of integrated management approaches that balance productivity with biodiversity conservation in agroforestry landscapes.